Assessment of the Impacts of Climate Variability on Hydropower Generation: A case study of the New Pangani Falls, Tanzania - Byarufu, Dativa; Katima, Jamidu; Said, Mahir (Tanzania Journal of Engineering and Technology, 2021)
Climate change poses potential impacts on hydropower generation either positively by increasing or negatively by decreasing river flow. This study assessed the impacts of climate variability on hydropower with a focus on the New Pangani Falls in Tanzania. Rainfall and temperature time series data from 1980-2014 were analyzed in relation to river discharge and associated impacts to hydropower generation. The Man-Kendall test was used to detect trend in both annual and seasonal time series. The results showed a negative trend in annual rainfall with Z= -2.41 at Î± = 0.05 and the slope Q = -0.964. Seasonal trend analysis showed that the amount of rainfall received during both dry and wet seasons has been decreasing. Positive trend was observed in both average annual maximum and minimum temperature series at Î± = 0.1 with Z = 1.73 and Î± = 0.001 with Z= 4.04, respectively and a positive slope for both. Analysis of regime shift at a 5% significant level showed that, rainfall in the New Pangani falls from 1980 to 2014 experienced two decreasing shifts both occurring in the last 15 years of analysis with a percentage of change of more than 10%. This strongly confirms climate variability in the study area. The study shows that hydropower generation depends strongly on the river inflow to the dam (r = 0.98) while changes in temperature do not affect the functioning of the hydropower plant as depicted by the weak linear relationship between temperature, rainfall (r = 0.085) and power generation (r = -0.082). It can be concluded, therefore, that river discharge variability in catchment has an adverse impact on hydropower generation in hydropower plant. Keywords: Climate variability, Hydropower generation, New Pangani Falls, Man-Kendall test, Rainfall.